Epidemiology of infections following haploidentical peripheral blood hematopoietic cell transplantation. Issue 1 (28th December 2016) - Slade, Michael; Goldsmith, Scott; Romee, Rizwan; DiPersio, John F.; Dubberke, Erik R.; Westervelt, Peter; Uy, Geoffrey L.; Lawrence, Steven J.
Abstract: Background: The use of T‐cell replete haploidentical hematopoietic cell transplant (haplo‐HCT) has increased substantially since the introduction of post‐transplant cyclophosphamide (PTCy) regimens. Limited data exist concerning infectious complications of haplo‐HCT utilizing mobilized peripheral blood (PB) hematopoietic cells. Methods: This retrospective cohort study included all adult patients at our institution undergoing PB haplo‐HCT with PTCy between June 2009 and June 2015. Infections were microbiologically confirmed. Invasive fungal infections (IFI) classified as "proven" or "probable" by standard definitions were included. Results: In total, 104 patients were identified. Median follow‐up was 218 days (range: 6–1576). A total of 322 episodes of infection were recorded. Eighty‐nine percent of patients experienced at least one infection. Median time to first infection was 22 days. Patients experiencing at least one bacterial, viral, and IFI were 62%, 72%, and 6%, respectively. The majority (69%) of bacterial infections were caused by enteric organisms. Seven cases of Staphylococcus aureus infection were recorded, with one bacteremia case. Cytomegalovirus (CMV) viremia occurred in 54/71 (76%) at‐risk patients at a median time of 24 days. Sixteen (15%) patients developed CMV disease. Nineteen percent (20/104) of patients developed BK polyomavirus‐associated cystitis. Six (6%) patients experienced a total of seven IFI. Infection was the primary cause of death for 12% (6/51) of patients and was a secondary cause for 41%. Conclusion: In PB haplo‐HCT patients, a high incidence of CMV viremia and disease was observed. Infections with enteric bacteria were common. Fungal and staphylococcal infections were uncommon. Further studies are needed to compare infectious complications in haplo‐HCT with other transplant modalities.